Ghrelin alleviates high glucose-induced retinal microvascular endothelial cell injury by activating Nrf2/HO-1 pathway to inhibit ferroptosis - Fen-Fen Wang; Rong Li; Dan Liao; Chao-Qun Liu; Xiao-Li Yang (International Journal of Ophthalmology)
AIM: To investigate the protective role of ghrelin against diabetic retinopathy (DR), focusing on its anti-ferroptotic mechanism in high glucose-induced retinal endothelial injury. METHODS: First, small interfering RNA (siRNA)-mediated interference was conducted to knockdown nuclear factor erythroid 2-related factor 2 (Nrf2). Using reverse transcription-polymerase chain reaction (RT-PCR), the expression level of Nrf2 was determined from human retinal microvascular endothelial cells (HRMECs) transfected with either si-NC or si-Nrf2. After that, cells were treated with 10 nmol/L ghrelin and then cultured in a high glucose (30 mmol/L) environment. EdU assay was utilized to assess cell proliferation, while transmission electron microscopy was employed to observe mitochondrial morphology. Flow cytometry was used to measure the level of intracellular reactive oxygen species (ROS), and biochemical assays were conducted to detect malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), and ferrous iron (Fe2+). Western blotting was used to identify the presence of ferroptosis-related proteins such as glutathione peroxidase 4 (GPX4), solute carrier family 7 member 11 (SLC7A11), Nrf2, and haem oxygenase-1 (HO-1). RESULTS: Under a high glucose environment, ghrelin could significantly promote the proliferation of HRMECs and mitochondrial status, remarkably decrease the levels of intracellular ROS and MDA, and up-regulate the level of GSH and SOD. Besides, ghrelin greatly reduced Fe2+ level in the cells while increased protein levels of GPX4 and SLC7A11. Subsequently, we found that high glucose induced inactivation of Nrf2/HO-1 axis and the protein expression profile were significantly promoted by ghrelin. Moreover, silencing of Nrf2 by siRNA delivery markedly diminished the changes induced by ghrelin in high glucose-induced HRMECs, shown as reduced cell proliferation and increased mitochondrial malformation, up-regulated ROS, MDA, Fe2+, GPX4 and SLC7A11, as well as down-regulated GSH, SOD, Nrf2 and HO-1. CONCLUSION: Ghrelin attenuates high glucose-induced injury of retinal endothelial cells via inhibiting ferroptosis, and activation of Nrf2/HO-1 pathway may be one of the mechanisms involved in this effect of ghrelin.